2015
DOI: 10.1371/journal.ppat.1005050
|View full text |Cite
|
Sign up to set email alerts
|

Lv4 Is a Capsid-Specific Antiviral Activity in Human Blood Cells That Restricts Viruses of the SIVMAC/SIVSM/HIV-2 Lineage Prior to Integration

Abstract: HIV-2 and SIVMAC are AIDS-causing, zoonotic lentiviruses that jumped to humans and rhesus macaques, respectively, from SIVSM-bearing sooty mangabey monkeys. Cross-species transmission events such as these sometimes necessitate virus adaptation to species-specific, host restriction factors such as TRIM5. Here, a new human restriction activity is described that blocks viruses of the SIVSM/SIVMAC/HIV-2 lineage. Human T, B, and myeloid cell lines, peripheral blood mononuclear cells and dendritic cells were 4 to >1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 109 publications
2
35
0
Order By: Relevance
“…Thus, the factor responsible for the marmoset B-LCL block probably exerts its action in the nucleus. The mechanism of action of this factor resembles the recently reported Lv4 activity that blocks viruses of the SIV mac /SIV sm /HIV-2 lineage in human blood cells42. In that work, Pizzato and colleagues also showed that the Lv4 activity targets the capsid of SIV mac , SIV sm , and HIV-2.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Thus, the factor responsible for the marmoset B-LCL block probably exerts its action in the nucleus. The mechanism of action of this factor resembles the recently reported Lv4 activity that blocks viruses of the SIV mac /SIV sm /HIV-2 lineage in human blood cells42. In that work, Pizzato and colleagues also showed that the Lv4 activity targets the capsid of SIV mac , SIV sm , and HIV-2.…”
Section: Discussionsupporting
confidence: 60%
“…Arsenic trioxide treatment has been shown to suppress the antiviral activity of TRIM5α, Lv4, and a post-entry inhibitory factor present in dendritic cells (DC)404142. We found that treatment with arsenic specifically increased the infectivity of HIV-1 in the marmoset B-LCLs, whereas HIV-1 infectivity decreased in the human B-LCLs; the observed decrease in the human B-LCLs may have possibly resulted from non-specific toxic effects of the treatment.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Host Lv2 protein has HIV-2 specific envelope restriction function (McKnight et al, 2001). Recently Lv4 was reported to be another capsid specific host restriction factor inhibiting SIV mac and HIV-2 infection (Pizzato et al, 2015). Several studies have reported that host sterile alpha motif (SAM) and histidine/aspartic acid (HD) domain protein 1 (SAMHD1) acts as a myeloid specific host anti-HIV/SIV restriction factor (Hrecka et al, 2011; Laguette et al, 2011).…”
Section: Introductionmentioning
confidence: 99%